2014
DOI: 10.1007/s11356-014-3601-5
|View full text |Cite
|
Sign up to set email alerts
|

Green waste compost as an amendment during induced phytoextraction of mercury-contaminated soil

Abstract: Phytoextraction of mercury-contaminated soils is a new strategy that consists of using the higher plants to make the soil contaminant nontoxic. The main problem that occurs during the process is the low solubility and bioavailability of mercury in soil. Therefore, some soil amendments can be used to increase the efficiency of the Hg phytoextraction process. The aim of the investigation was to use the commercial compost from municipal green wastes to increase the efficiency of phytoextraction of mercury-contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 37 publications
3
46
0
Order By: Relevance
“…The comparison analysis of results obtained for blank and control treatments pointed that combined use of compost + NTA increased L. sativum L. growth. The earlier study demonstrated that compost can stimulate the plant growth due to increasing macro‐ and micro‐elements input to the soil . However, the use of NTA as a growing medium component did not show toxicity symptoms, which is in agreement with results obtained by Quartacci et al The moderate concentration of NTA was not phytotoxic to Brassica juncea L. while its higher concentrations reduced dry weight of plant shoots .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The comparison analysis of results obtained for blank and control treatments pointed that combined use of compost + NTA increased L. sativum L. growth. The earlier study demonstrated that compost can stimulate the plant growth due to increasing macro‐ and micro‐elements input to the soil . However, the use of NTA as a growing medium component did not show toxicity symptoms, which is in agreement with results obtained by Quartacci et al The moderate concentration of NTA was not phytotoxic to Brassica juncea L. while its higher concentrations reduced dry weight of plant shoots .…”
Section: Resultssupporting
confidence: 88%
“…Lepidium sativum L. is a fast growing plant that is characterized by low nutrition requirements. The plant showed its potential in Cd, arsenic (As) and Hg accumulation . The previous study of Smolinska 27 demonstrated that this plant species is able to translocate Hg to its aerial tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Smolinska (2015) showed that application of compost to the polluted soil may lead to formation of organic matter complexes with Hg, which in turn lead to decreasing Hg toxicity. On the other hand, CA enhanced other heavy metal accumulation (like Cd) because of its chelating ability (Ehsan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, applying ammonium thiosulfate increased Hg accumulation in the shoot tissues of B. juncea from <1 to >40 mg kg −1 at a site containing Hg at 2.82 mg kg −1 of soil. Smolinska (2014) recently investigated the enhanced phytoextraction of mercury-contaminated soil by Lepidium sativum L. using green waste compost as an amendment. The green compost was composed of leaves, grasses, branches, and other green wastes and, therefore, had high content of organic matters.…”
Section: Other Promising Technologiesmentioning
confidence: 99%